POST HARVEST TREATMENTS AND HEAVY METAL CONTENT IN THE EGG MASS OF WEDGE SEAHARE DOLABELLA AURICULARIA (LIGHTFOOT, 1786) - Delan, Gloria; Pepito, Ador R; Abdon, Hector C; Lamayo, Ma. Helian A; Aballe, Ricardo S; Lamayo, Roberto C (Journal of Agriculture and Technology Management, 2015)
The egg mass or “lukot” of the wedge sea hare D. auricularia has been collected by gleaners from the wild of which its safety as food for human is not yet ascertain particularly the presence of heavy metals. The said egg mass has been consumed as food but prior to its consumption, these are usually subjected to post-harvest treatment. Thus, this study assessed the effect of the different post- harvest treatment with fresh as control (T1), with vinegar (T2), boiling (T3) and the combination of boiling and vinegar (T4). Results show that the heavy metals determined from the treated egg mass were chromium, cobalt, copper, lead, nickel, gold, mercury and manganese and are expressed in terms of mg metals/kg sample. It further shows that in terms of chromium all samples have less than 0.60, cobalt has less than 2.0, copper has less than 0.10, gold has less than 0.30, and lead has less than 1.50. In terms of the effect of postharvest treatment, nickel in T1 has less than 0.30, while T2 has 0.66 (±0.07), T3 has 0.56 (±0.05), T4.has 0.41(±0.07). In terms of mercury, it has 187(±33) for T1, 383 (±5) for T2, 123(±26) for T3 and 185(±42) for T4. In terms of magnesium, T1 has 0.67 (±0.05), T2 has 0.66 (±0.66), T3 has0.55(±0.08) and T4 has 0.41(±0.10). Results indicate that the egg mass of the wedge sea hare contains heavy metals but most of them had an amount lower than the prescribed standard levels, except the amount of mercury.